(untitled) - Sevenair, John P. (Dubuque, Iowa, 1996)
Help your students gain a solid understanding of central chemical principles with this supportive introductory chemistry text. Addressing the needs of students of varied backgrounds, authors Burkett and Sevenair emphasize skill-building, analytical thinking, real-life applications, and the history of science and the scientific process.
Keywords: Chemistry